Seguridad turística y nivel de satisfacción del turista nacional en la ciudad de Iquitos, periodo 2023 - Falcon Leon, Rosmeri Valeria (2024)
The study examined the interaction between tourist safety and the satisfaction level of domestic tourists in the city of Iquitos in 2023. It employed a quantitative, descriptive-correlational, and non-experimental approach, evaluating the perceptions of 380 tourists selected through probabilistic sampling. Using a questionnaire designed according to the indicators of the variables of interest, relevant information for the analysis was collected. The results indicated that the management of tourist safety and its perception significantly impact tourist satisfaction. A strong positive correlation (Spearman's correlation coefficient of 0.912) between tourist safety and tourist satisfaction was found, demonstrating the importance of safety as a key factor for a satisfactory tourist experience. Despite some challenges identified in the management of tourist safety, the majority of visitors expressed high levels of satisfaction with their experience in Iquitos. The study underscores the need for continuous improvement in tourist safety and management strategies to ensure positive experiences that encourage repeat visits and recommendations. It is concluded that tourist safety plays an essential role in the satisfaction of domestic tourists, reinforcing the need for policies and practices focused on safety as a critical component of the tourist offer in Iquitos.